A nonparametric economic index to measure the collective effort of national-level economic activities directed towards greater efficiency - Armando Elizondo-Noriega; Idalia Estefania Ponce-Jaramillo; Sonia Valeria Avilés-Sacoto; David Güemes-Castorena; Víctor G. Tercero-Gómez; Naveen Tiruvengadam; Mario G. Beruvides (Cogent Economics & Finance, 2019)
For an economic system such as a nation, assessing the efforts of its constituent economic activities that are directed toward greater efficiency, which in aggregate determines the overall efficiency at the national level is important. Such an exercise provides information on which constituent economic activities are underperforming and require attention. This article presents an economic performance index called the Efficiency Effort Index (EE-Index) that measures such efforts of economic activities directed at efficiency improvement. This nonparametric, dimensionless index is computed based on a combination of Leveled-Data-Envelopment-Analysis (LDEA) and Markov Chains (MCs). LDEA compares diverse decision-making units to yield a set of efficiency scores, which are first discretized and then subjected to first-order MC treatment. The EE-Index was computed for a chosen nation and compared with that nation's average relative efficiency (ARE) score, another performance index presented in this study, and GDP per capita. This comparison suggested that the slow growth in the chosen country's GDP coincided with a general declining trend exhibited in the country's efforts and aggregate efficiency achieved by these efforts, measured, respectively, by the EE-Index and the ARE-Index.
Keywords: B41; C14; C43; O25; 330; economic activities; national efficiency; national productivity; global economic-performance index